Actor-network theory in consolidating collaborative web platform methodology for knowledge collaboration - Omar, Mohd Adan; Ibrahim, Amal; Ibrahim, Huda (2012)
Knowledge collaboration has been implemented in variety of ways to creates the knowledge sharing and individual knowledge, talents and information can be effectively used.Knowledge collaboration is all about relation and connection of involved actors and this cannot be separated. This relationship is translated through an Actor-Network Theory, which is a sociology theory.This research is to study how sociology theory can be used as an interpreting and solution tool in information system field, in this case for creating a collaborative web platform.This research shows how Actor-Network Theory can be embedded to system development methodology such as identifying list of requirements, analyzing current system and identifying the actor’s roles, but for the purpose of this article (at this stage) there is no research result presented.